PRINCIPLES OF INTERACTION IN THE TOPOLOGY OF ANTINOMIES (ONTOLOGICAL DECONSTRUCTION OF THE SOCIAL MATRIX) - Kharchenko, Julia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
The phenomenon of interaction: describes the configuration of the social matrix in its dynamics; fixes the continuous variability of reality; actualizes the need to maintain balance in nature, as well as to preserve the harmonious dualism of human bodily and spiritual constructs. Interaction is defined as an antinomic opposition, which can be considered in terms of symmetry and asymmetry. The phenomenon of interaction is considered in the philosophical-methodological, ontological and metaphysical aspects of deconstruction when analyzing the antinomian characteristics of interaction.